Genome Sequence of Naturally Competent Aggregatibacter actinomycetemcomitans Serotype a Strain D7S-1 - Chen, Casey (American Society for Microbiology (ASM), 2010)
The major clonal lineages of the Gram-negative periodontal pathogen Aggregatibacter actinomycetemcomitans include serotype a, b, and c strains. Here, we report the draft genome sequence of a naturally competent serotype a strain, D7S-1, isolated from a patient with aggressive periodontitis.